Do Open Borders Tempt a Saint? Evidence from Schengen on Crime Rates in German Border Regions - Pia Wassmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The abolishment of passport and any other type of border controls at the German-Polish and German-Czech border in December 2007 provoked public concerns that open border would increase cross-border crime. Despite these widespread concerns, empirical research on whether the public fears were justified is still scarce. Based on data from the official German Police Crime Statistic, the paper evaluates whether the implementation of the Schengen Agreement in Poland and the Czech Republic in December 2007 affected crime rates in German regions bordering these two countries. Effects are identified by regression-adjusted difference-in-difference estimation on matched samples that allows evaluating the Schengen effects in a causal way. Preliminary results show that no significant Schengen effect can be observed for the most common types of criminal offenses. These findings suggest that in contrast to public concerns, German NUTS3 regions bordering Poland and the Czech Republic have not experienced an increase in crime as a result of the implementation of the Schengen Agreement of its Eastern neighbors. In light of the current discussion on the future of the Schengen zone and borderless Europe, this is quite an important result.
Keywords: R10; K40; F60; 330